Effectiveness of Teacher Performance in Maximizing Student's Expressive Writing in Science Learning at Sebatik Vocational School - Mumun Prasetyani; Nanang Erma Gunawan (Postgraduate, University of Mataram, 2024)
Adolescence is an important phase in individual development where massive changes occur, both physically and psychologically. Research shows that teenagers often have difficulty managing and expressing their emotions appropriately, which can impact their emotional and social well-being. This research aims to test the effectiveness of teacher performance in improving students' expressive writing skills in science learning at Sebatik Vocational School. The research method used is quantitative experimental research with a one group pretest-posttest design. Eight students who experienced difficulties in expressive writing skills were included in this study. Data was obtained through pretest and posttest conducted after providing teacher performance services. The results of the analysis using the Wilcoxon Signed Ranks test showed that there was a significant increase in students' expressive writing abilities after being provided with teacher performance services. The calculated z value was -2.521>z table (1.96) at a significance level of α=0.05. Asymp probability value. Sig. (2-tailed) is 0.012<of α = 0.05, so the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Thus, the teacher's service performance in providing students' expressive writing skills at Sebatik Vocational School has proven to be effective in improving students' expressive writing abilities in science learning.